Cloning of nitric oxide associated 1 (NOA1) transcript from oil palm (Elaeis guineensis) and its expression during Ganoderma infection - Kwan, Yee-Min; Meon, Sariah; Ho, Chai-Ling; Wong, Mui-Yun (Elsevier, 2015)
Nitric oxide associated 1 (NOA1) protein is implicated in plant disease resistance and nitric oxide (NO) biosynthesis. A full-length cDNA encoding of NOA1 protein from oil palm (Elaeis guineensis) was isolated and designated as EgNOA1. Sequence analysis suggested that EgNOA1 was a circular permutated GTPase with high similarity to the bacterial YqeH protein of the YawG/YlqF family. The gene expression of EgNOA1 and NO production in oil palm root tissues treated with Ganoderma boninense, the causal agent of basal stem rot (BSR) disease were profiled to investigate the involvement of EgNOA1 during fungal infection and association with NO biosynthesis. Real-time PCR (qPCR) analysis revealed that the transcript abundance of EgNOA1 in root tissues was increased by G. boninense treatment. NO burst in Ganoderma-treated root tissue was detected using Griess reagent, in advance of the up-regulation of the EgNOA1 transcript. This indicates that NO production was independent of EgNOA1. However, the induced expression of EgNOA1 in Ganoderma-treated root tissues implies that it might be involved in plant defense responses against pathogen infection.